2020
DOI: 10.26714/lensa.10.2.2020.206-217
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English at Junior High School in Indonesian Rural Area : The Implementation of Scientific Approach

Abstract: The creation of the curriculum aims to improve the quality of education in the country. It is also happening in  Indonesia, where the curriculum is always created with the aim of improving the quality of education in Indonesia. The aim of this study was to investigate the implementation of a scientific approach to teaching English in Junior High School in the Indonesian rural areas context. Qualitative method used in this study on pilot project school of 2013 curriculum. The research subject was the English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Only one out of every eight Atambua students had a multilingual background, using three languages to achieve the highest level (3), despite learning English during the golden period. Malaikosa & Taopan (2020). Too many students, inadequate time, and a lack of teaching resources were all issues with applying scientific processes to teach English in junior high school in rural locations (especially Alor).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one out of every eight Atambua students had a multilingual background, using three languages to achieve the highest level (3), despite learning English during the golden period. Malaikosa & Taopan (2020). Too many students, inadequate time, and a lack of teaching resources were all issues with applying scientific processes to teach English in junior high school in rural locations (especially Alor).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Alor Regency, the researchers have proven that there were some problems in implementing the EFL curriculum 2013: Teachers have difficulties in making lesson plans, implementing the scientific approach in the classroom, doing an authentic assessment, and lack of learning resources (Malaikosa & Sahayu, 2019). In addition, Malaikosa & Taopan (2020) found that other problems in using the scientific steps on teaching English were too many students, limited allocation time is given, and lack of teaching sources. Therefore, the competencies of EFL teachers in NTT need to be promoted and developed in order to improve the quality of education in the area.…”
Section: Discussionmentioning
confidence: 99%
“…There were several previous research related to teaching speaking in the Indonesian context. The first previous research was entitled Teaching English at Junior High School in Indonesian Rural Area: The Implementation of Scientific Approach (Malaikosa & Taopan, 2020). The result showed that there were some problems in applying the teaching method in teaching English in the rural area.…”
Section: Introductionmentioning
confidence: 99%
“…English teaching and learning process is essential to conduct to improve the ability of language in many kinds of communication contexts in daily life (Malaikosa & Taopan, 2020). However, has globally spread and damaged all fields, including education (Ma'rifah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%